Cross-cultural insights into non-communicable disease perceptions: a five-nation survey - Carlos O Mendivil; Jorge A Rios-Duarte; Ricardo A Peña-Silva (BMJ Public Health)
Background Non-communicable diseases (NCDs) pose a significant global health challenge, with varying perceptions and attitudes influencing public health responses and policy development. This study aims to elucidate the cross-cultural perceptions and attitudes towards NCDs across five diverse countries, providing insights into global public health strategies.Methods We analysed data from the ‘Measuring Public Perceptions of Noncommunicable Diseases’ survey, developed by Gallup and conducted in Colombia, India, Jordan, Tanzania and the USA. The survey encompassed questions on the perceived harmfulness of NCDs, empowerment for risk reduction and the influence of various entities on health. Statistical analysis included bivariate and multiple logistic regression models to assess the impact of socio-demographic factors on these perceptions.Findings The study revealed significant cross-country variations in the perception of NCDs’ harmfulness and the public’s empowerment to reduce their risk. High-income and education levels were consistently associated with a greater perception of NCD harmfulness and empowerment across the surveyed nations. Notably, the USA exhibited a paradoxical trend of high empowerment and knowledge levels about NCDs, but low support for health policies like increased taxes on sugary beverages and alcohol. The proportion of participants from India and Jordan who manifested they could take actions to modify their risk of NCDs was remarkably low. Tanzanian and Jordanian respondents, especially female, showed lower empowerment levels, highlighting cultural and socioeconomic disparities in health literacy and policy support.Interpretation These findings underscore the complexity of addressing NCDs globally and point to the need for culturally and socioeconomically tailored public health interventions. Understanding local perceptions and attitudes is crucial for designing effective health literacy programmes and policies to mitigate NCD risks.